Metabolic profiling of glucosinolates and their hydrolysis products in a germplasm collection of Brassica rapa turnips. (October 2017) - Klopsch, Rebecca; Witzel, Katja; Börner, Andreas; Schreiner, Monika; Hanschen, Franziska S.
Abstract: About 10% of the world's vegetable production is generated from Brassicaceae, wherein Brassica rapa is a dominating species. There is growing evidence that glucosinolates (GLSs), main plant secondary metabolites in Brassicales, play an important role in promoting human health. Natural genetic diversity of B. rapa can be explored for vegetable improvement. We analyzed leaves and tubers of 16 B. rapa turnips for their GLS composition by UHPLC-DAD and the corresponding hydrolysis products by GC–MS. Thirteen GLSs were identified, 8 aliphatic, 4 indolic and one aromatic. 3-Butenyl GLS was prevailing in both plant organs while in tubers 2-hydroxy-3-butenyl GLS and 2-phenylethyl GLS occurred in high amounts. A total of 24 GLS breakdown products were detected in tubers and 16 in leaves. Epithionitriles were the main hydrolysis products in both plant organs with 4, 5-epithiopentanenitrile and 3-hydroxy-4, 5-epithiopentanenitrile being the main compounds. When comparing leaves and tubers, an accumulation of GLSs and their breakdown products was observed in tubers compared to leaves. Our analysis achieved the comprehensive profiling of all GLS metabolites in a collection of B. rapa turnips, underlining the natural variation not only of intact GLS, but also of their breakdown products. Graphical abstract: Highlights: Quantification of B. rapa turnips regarding glucosinolates and breakdown products. Pattern of glucosinolates and breakdown products are accession- and organ-specific. Epithionitriles are major breakdown products in leaves. Tuber breakdown products are epithionitriles, nitriles, isothiocyanates.